Implications of TGFβ Signaling and CDK Inhibition for the Treatment of Breast Cancer - Joseph T. Decker (MDPI AG, 2021)
TGFβ signaling enacts tumor-suppressive functions in normal cells through promotion of several cell regulatory actions including cell-cycle control and apoptosis. Canonical TGFβ signaling proceeds through phosphorylation of the transcription factor, SMAD3, at the C-terminus of the protein. During oncogenic progression, this tumor suppressant phosphorylation of SMAD3 can be inhibited. Overexpression of cyclins D and E, and subsequent hyperactivation of cyclin-dependent kinases 2/4 (CDKs), are often observed in breast cancer, and have been associated with poor prognosis. The noncanonical phosphorylation of SMAD3 by CDKs 2 and 4 leads to the inhibition of tumor-suppressive function of SMAD3. As a result, CDK overactivation drives oncogenic progression, and can be targeted to improve clinical outcomes. This review focuses on breast cancer, and highlights advances in the understanding of CDK-mediated noncanonical SMAD3 phosphorylation. Specifically, the role of aberrant TGFβ signaling in oncogenic progression and treatment response will be examined to illustrate the potential for therapeutic discovery in the context of cyclins/CDKs and SMAD3.